Economic relevance and adoption of monitoring and management of the fruit fly in citrus orchards of western Santa Catarina (Revista de Ciências Agroveterinárias, 2023)
The west of Santa Catarina is the main citrus producing region in the state. The objective of this work was to carry out a survey about the citriculture economic relevance and the monitoring and management of fruit flies by citrus growers in the west of Santa Catarina. A questionnaire with 13 questions was applied in loco to 58 citrus growers and the responses were organized for results analysis. In the west of Santa Catarina, for most of the respondents (67.8%), the citriculture is a complementary activity of another main activities practiced in the farm. Most citrus growers (91.38%) consider the fruit fly one of the main phytosanitary problems of the crop and only 12.07% report a low level of incidence of this pest in their orchards. However, most farmers do not monitor the insect (41.4%) or are unaware of the subject (13.8%). Of those who monitor, 56.25% use traps, while 43.75% monitor by visual observation of the fruits. Chemical control is carried out by almost half of citrus growers, erroneously based on the presence of fallen fruit or even by calendar applications. These presented data are worrying and reveal the negligence of citrus growers with the practice of monitoring this important pest.
Keywords: Anastrepha fraterculus; orange; tangerine; integrated pest management; environmental monitoring; citrus